Assessing the Acceptability and Usability of an Interactive Serious Game in Aiding Treatment Decisions for Patients with Localized Prostate Cancer - Reichlin, Lindsey; Mani, Nithya; McArthur, Kara; Harris, Amy M; Rajan, Nithin; Dacso, Clifford C (Journal of Medical Internet Research, 2011)
BackgroundMen diagnosed with localized prostate cancer face a potentially life-altering treatment decision that can be overwhelming. Enhancing patient knowledge through education can significantly reduce feelings of uncertainty while simultaneously increasing confidence in decision making. Serious games have been shown in other populations to increase health knowledge and assist with the health decision-making process. We developed an interactive serious game, Time After Time, which translates evidence-based treatment outcome data into an accessible and understandable format that men can utilize in their prostate cancer treatment decision-making process. The game specifically aims to raise men’s awareness and understanding of the impact of health-related quality of life issues associated with the major treatment options and to enrich their conversations with their health care providers. ObjectiveThis study determined the acceptability and usability of the alpha version of Time After Time, an interactive decision aid for men diagnosed with localized prostate cancer, in order to inform future iterations of the serious game. MethodsThe study employed a mixed methods approach to assess the acceptability and usability of the Time After Time serious game using qualitative focus groups and a quantitative Likert scale survey. ResultsA total of 13 men who had already completed treatment for localized prostate cancer completed the survey and participated in focus group meetings. The majority of the study participants rated Time After Time as an appropriate decision tool for localized prostate cancer and verified that it meets its goals of increasing focus on side effects and generating questions for the patient’s health care team. However, participants also expressed concerns about game usability and the diversity of information covered regarding treatment options and potential treatment outcomes. ConclusionsSerious games are a promising approach to health education and decision support for older men. Participants were receptive to the idea of a serious game as a decision aid in localized prostate cancer. However, usability issues are a major concern for this demographic, as is clarity and transparency of data sources.